A comparative review: effect of thermal and non-thermal treatment towards the physicochemical characteristics of stingless bee honey / Noor Syaza Aqilah Amran and Mohd Hilmi Hassan - Amran, Noor Syaza Aqilah; Hassan, Mohd Hilmi (2021)
Stingless bee or Kelulut honey is known to have a higher water content compared to other types of honey that may reach up to 28%. Malaysian Standard has stated that a good quality of Kelulut honey shall have a water content of not more than 17%. Hence, many approaches, including thermal and non-thermal treatment, have been done to reduce its moisture content. This is because high water content may lead to quality degradation of Kelulut honey. This review aims to compare the effect of both thermal and non-thermal treatment towards the physicochemical characteristics such as moisture content, viscosity, colour, total phenolic content, 5- hydroxymethylfurfural (HMF), diastase activity, and antioxidant activity (DPPH) of stingless bee honey. Numbers of studies reported that both treatments were able to reduce the moisture to a level recommended by the Malaysian Standard. The results also showed that other physicochemical characteristics of stingless bee honey were altered after both treatments, highlighting the changes of honey to become more viscous and darker colour, and increasing in phenolic content. On the other hand, the changes in diastase number and HMF are slightly different. As for thermal treatment, diastase number decreased and HMF increased with the temperature and contrariwise for the non-thermal treatment. To sum up, by implementing the right temperature and processing time, thermal treatment results in a better quality of dehydrated Kelulut honey.